Lipid-Lowering Effects of Alpha-Mangostin: A Systematic Review and Meta-Analysis in Hyperlipidemic Animal Models - Moragot Chatatikun; Aman Tedasen; Phichayut Phinyo; Pakpoom Wongyikul; Passakorn Poolbua; Wiyada Kwanhian Klangbud; Jason C. Huang; Rattana Leelawattana; Atthaphong Phongphithakchai (Foods)
Hyperlipidemia is a major risk factor for cardiovascular and metabolic diseases. Although pharmacologic treatments are effective, their adverse effects have spurred interest in natural alternatives. Alpha-mangostin (AM), a xanthone from Garcinia mangostana, has shown lipid-lowering effects in animal studies, but its overall efficacy remains unclear. This systematic review and meta-analysis, conducted in accordance with PRISMA 2020 guidelines, evaluated AM’s impact on lipid profiles in hyperlipidemic animal models. Databases including Scopus, PubMed, ScienceDirect, Cochrane Library, and Web of Science were searched for relevant controlled studies. Nine studies (N = 226 animals) met inclusion criteria, reporting data on triglycerides (TG), total cholesterol (TC), LDL-C, and HDL-C. Risk of bias, assessed using the Cochrane RoB 2 tool, was generally low-to-moderate. Meta-analysis using a random-effects model revealed that AM significantly reduced TG, TC, and LDL-C, while increasing HDL-C. Stronger effects were observed at doses <50 mg/kg/day. Subgroup and sensitivity analyses confirmed robustness and highlighted the influence of species, region, and treatment duration. These findings suggest that AM is a promising lipid-lowering agent in animal models. Further clinical trials are needed to validate efficacy in humans and determine optimal dosing.